Prepregnancy maternal diabetes combined with obesity impairs placental mitochondrial function involving Nrf2/ARE pathway and detrimentally alters metabolism of offspring. (January 2018) - Duan, Yang; Sun, Fuqiang; Que, Shengshun; Li, Yueqin; Yang, Suyan; Liu, Geli
Summary: Metabolic disorders usually increase the level of reactive oxygen species (ROS) and damage mitochondrial function. The placenta supplies nutrients and hormonal signals to the fetus for regulating fetal metabolism, and is also prone to injury by oxidants. The aim of this study was to determine the effect of pre-existing maternal type 2 diabetes mellitus (DM) combined with obesity on placental mitochondrial function and metabolism disorders of offspring. The study included 96 pregnant women. The women were put into the following groups: healthy women (control, n = 24), women with DM (DM, n = 24), women with obesity (OB, n = 24) and women with both DM and obesity (DM + OB, n = 24). The ROS level, mitochondrial content, and the mitochondrial respiratory complex activities of the placenta were measured in the four groups. The expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) was detected by immunofluorescence staining and western blotting. In addition, serum levels of insulin, glucose, leptin, nonesterified fatty acid (NEFA), adiponectin and triglycerides of their offspring were also measured. Maternal DM combined with obesity markedly increased ROS level, reduced mitochondrial DNA (mtDNA) content and mitochondrial respiratory complex I, II–III activities in placenta compared to the placenta from the control group and the DM group. Maternal DM combined with obesity significantly decreased Nrf2 and HO-1 expression. Furthermore, maternal DM combined with obesity influenced the glucose and lipid metabolism in their offspring. In conclusion, women with both DM and obesity detrimentally alter placenta function in oxidative stress regulation, and the Nrf2/ARE (antioxidant responsive element) pathway is involved. This may increase metabolic disturbance susceptibility in their offspring.